Targeting tumor angiogenesis and metabolism with photodynamic nanomedicine - Lv, Yong; Pu, Lihui; Ran, Bei; Xiang, Bo (Frontiers in Cell and Developmental Biology, 2025)
Photodynamic therapy (PDT) holds considerable promise as a tumor treatment modality, characterized by its targeted action, compatibility with other therapeutic approaches, and non - invasive features. PDT can achieve remarkable spatiotemporal precision in tumor ablation through the generation of reactive oxygen species (ROS). Nevertheless, despite its potential in tumor treatment, PDT encounters multiple challenges in practical applications. PDT is highly oxygen - dependent, and thus the effectiveness of PDT can be markedly influenced by tumor hypoxia. The co-existence of abnormal vasculature and metabolic deregulation gives rise to a hypoxic microenvironment, which not only sustains tumor survival but also undermines the therapeutic efficacy of PDT. Consequently, targeting tumor angiogenesis and metabolism is essential for revitalizing PDT. This review emphasizes the mechanisms and strategies for revitalizing PDT in tumor treatment, predominantly concentrating on interfering with tumor angiogenesis and reprogramming tumor cell metabolism. Lastly, the outlining future perspectives and current limitations of PDT are also summarized. This could provide new insights and methodologies for overcoming the challenges associated with PDT in tumor treatment, ultimately advancing the field of PDT.